Resilience of Parents with Autism Spectrum Disorder (ASD) in SLB Aisyiyah Tulangan Sidoarjo - Sari, Defi Kumala; Mariyati, Lely Ika (Indonesian Journal Publisher, 2024)
The purpose of this study is to characterize the traits and resilience variables of parents of children in SLB Aisyiyah reinforcing sidoarjo who have Autism Spectrum Disorder (ASD). The newly identified traits and elements that support parents of children with autism spectrum disorder (ASD) in finding resilience in accepting their child's diagnosis. This study employs a qualitative approach. by focusing on three pairs of parents of children with autism spectrum disorder who are between the ages of 28 and 35 and have overcome challenges to become resilient. The interview approach, which includes both field and general notes, is the technique used to obtain the dates. According to the study's findings, every parent of a kid with autism spectrum disorder (ASD) possesses insight, independence, relationships, initiative, creativity, humor, morality, and resilience. I have overcome adversity because I am capable of doing so. Each subject's faith and submission to Allah SWT's will are also influenced by other causes. However, there is a temporal discrepancy in the resilience process amongst the three subject parents of children diagnosed with autism spectrum disorder (ASD). The support of those closest to you has an impact on this since youngsters with Autism Spectrum Disorder (ASD) must overcome their challenges.